Formulation and optimization of medium-chain fatty acid nano-emulsion / Muhd Bahrudin Sari'at - Sari'at, Muhd Bahrudin (2009)
The aim of this study is to optimize the virgin coconut oil in formulation of nano-emulsion. In this study we prepare various formulations of emulsion consist of virgin coconut oil as disperse phase. From the formulations we prepare, we investigate the influences of Tween 80 as surfactant and Span 80 as co-surfactant in term of make the virgin coconut oil emulsion in nano range of size droplet. The result shows in ratio of 2:1 between virgin coconut oil and surfactant and ration 2:1 also between Tween 80 and Span 80 give us the smallest mean droplet size which is 0.186 µm. Moreover, we also investigate the nano-emulsion produced stability which we leave the nano-emulsion for one week in laboratory and measure the size particle again after that. The result was not significance change from 0.186 µm to 0.194 µm. As the conclusion, this research is really beneficial to optimize and find out the best possible formulation and production of the Virgin Coconut Oil nano-emulsion by self-emulsifying agent.